KNOWLEDGE AND PRACTICE OF SELF-MEDICATION AMONG UNDERGRADUATE BSN(GENERIC) STUDENTS - ULLAH , M; SADDIQUE , H; JABEEN , R (Biological and Clinical Sciences Research Journal, 2024)
Self-medication is a widespread practice globally, particularly among healthcare students, posing risks such as drug misuse, delayed treatment, and antimicrobial resistance. Nursing students, as future healthcare providers, are a key demographic for evaluating self-medication practices. Objective: To assess the knowledge and practices of undergraduate BSN (Generic) students regarding self-medication at Superior University, Lahore. Methods: A descriptive cross-sectional study was conducted among 140 BSN (Generic) students. Data were collected using a structured questionnaire covering demographic characteristics, knowledge, and self-medication practices. Descriptive and inferential statistics were analyzed using SPSS version 26.Results: The study found that 57.1% of participants engaged in self-medication, with 60% acknowledging its harmful effects but 66.4% incorrectly believing antibiotics were necessary for the common cold. Unsafe practices included reusing prescriptions (57.9%) and increasing drug doses without professional consultation (58.6%). A significant proportion (60%) also believed that expensive drugs are more effective. Conclusion: Despite moderate knowledge, unsafe self-medication practices are prevalent among nursing students. Targeted educational programs and stricter regulatory measures are essential to address these gaps and promote safe medication behaviours among future healthcare providers.